Orang Islam Jawa pesisiran - Thohir, Mudjahirin, 1954- (Semarang : Fasindo Press, 2006)
Religious and socioeconomic conditions of the Muslim communities in coastal areas of northern Java
Revision of the author's thesis (doctoral)--Universitas Indonesia, 2002
Includes bibliographical references (p. [343]-363)
Keywords: Islam -- Indonesia -- Java; Muslims -- Religions life -- Indonesia -- Java; Muslims -- Indonesia -- Java -- Social conditions; Java (Indonesian) -- Religions life and customs